2006
DOI: 10.1016/j.tplants.2006.10.007
|View full text |Cite
|
Sign up to set email alerts
|

How do plants respond to nutrient shortage by biomass allocation?

Abstract: Plants constantly sense the changes in their environment; when mineral elements are scarce, they often allocate a greater proportion of their biomass to the root system. This acclimatory response is a consequence of metabolic changes in the shoot and an adjustment of carbohydrate transport to the root. It has long been known that deficiencies of essential macronutrients (nitrogen, phosphorus, potassium and magnesium) result in an accumulation of carbohydrates in leaves and roots, and modify the shoot-to-root b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

58
693
8
23

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 999 publications
(811 citation statements)
references
References 79 publications
58
693
8
23
Order By: Relevance
“…Further, the high expression of IbVP1 in young storage root indicates an important function related to storage root development (Figure 2). These results further confirmed that up‐regulation of H + ‐PPase promoted translocation of photosynthates from leaf to root, as hypothesized previously (Gaxiola et al ., 2012; Hermans et al ., 2006; Khadilkar et al ., 2016; Paez‐Valencia et al ., 2011). A recent study also demonstrated that increased sucrose accumulation was required for the regulation of auxin‐mediated Fe deficiency in plants (Lin et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the high expression of IbVP1 in young storage root indicates an important function related to storage root development (Figure 2). These results further confirmed that up‐regulation of H + ‐PPase promoted translocation of photosynthates from leaf to root, as hypothesized previously (Gaxiola et al ., 2012; Hermans et al ., 2006; Khadilkar et al ., 2016; Paez‐Valencia et al ., 2011). A recent study also demonstrated that increased sucrose accumulation was required for the regulation of auxin‐mediated Fe deficiency in plants (Lin et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Translocation of accumulated nitrogen reserves from older to newer tissues is achieved by the programmed turnover of cellular components, a process in which protein degradation plays a central role (Agren, 1985;McConnaughay and Coleman, 1999;Lemaire et al, 2008;Kraiser et al, 2011). This mechanism becomes systemic under conditions of nitrogen limitation, due to the need to triage constituents, and completion of the life cycle becomes prioritized over vegetative growth (Carter and Knapp, 2000;Tranbarger et al, 2003;Zhao et al, 2005;Hermans et al, 2006). The composition of cells is changed as organs enter senescence leading to lower protein accumulation, a process that requires the active participation of a large suite of proteases as well as the ubiq-uitin-proteasome system.…”
Section: Discussionmentioning
confidence: 99%
“…As diferenças ocorridas entre os tratamentos adubados e não adubados, tal como a diferença entre os adubos orgâni-cos (AO) e organominerais (AOM), podem ser explicadas quando se considera que o adubo mineral disponibiliza maior quantidade de nutrientes permitindo maior alocação de biomassa que em combinação com o adubo orgânico, o que pode ter contribuído para a elevação da CTC e melhoria das condições físicas do solo, fato já comprovado em vários trabalhos (Ferreira & Oliveira, 2003;Farias, 2004;Hermans et al, 2006;Oliveira et al, 2006).…”
Section: Comprimento Da Haste Floral (Chf)unclassified
“…Em geral, nas flores de corte a reserva de carbono contida na haste é utilizada para estender a longevidade potencial das flores e, quanto maior o comprimento e o diâmetro da haste maior também a durabilidade pós-colheita (Hermans et al, 2006, Castro et al, 2007.…”
Section: Diâmetro Da Haste Floral (Dhf)unclassified